Forest conversion induces seasonal variation in microbial β‐diversity. (11th January 2018) - Liu, Shengen; Wang, Hang; Deng, Ye; Tian, Peng; Wang, Qingkui
Summary: World‐wide conversion of natural forests to other land uses has profound effects on soil microbial communities. However, how soil microbial β‐diversity responds to land‐use change and its driving mechanisms remains poorly understood. In this study, therefore, we examined the effect of forest conversion from native broad‐leaved forest to coniferous plantation on soil microbial β‐diversity and its underlying mechanisms in both summer and winter in subtropical China. Microbial communities increasingly differed in structure as geographical distance between them increased, and the slope of the relationship among distances and community similarity differed among forest covers. In general, as with microbial β‐diversity, slopes also shifted across seasons. Finally, null deviations of bacterial and fungal communities were lower in coniferous plantation and presented opposing seasonal variations with greater influences of deterministic processes in summer for soil fungi and in winter for soil bacteria. Integrating previous frameworks with our β‐null model results, we propose a conceptual model to link microbial secondary succession to stochastic/deterministic shifts in forest ecosystems. Overall, forest conversion induced significant increases in stochastic processes in both bacterial and fungal community assemblies. Therefore, our results highlight the importance of spatiotemporal scales to assess the influence of land‐use change on microbial β‐diversity.